The Influence of Product Quality and Price On Consumer Purchasing Decisions CV Tunas Mandiri - M Azril; Siti Komariah Hildayanti; Meilin Veronica (ProBisnis : Jurnal Manajemen, 2023)
Factors that can influence purchasing decisions are product quality and price. This study aims to examine the effect of product quality and price on consumer purchasing decisions. This research begins with a preliminary survey of 10 stores as a sample of respondents who are consumers of CV. Tunas Mandiri. The population in this study was 60 building stores. The sample is determined by taking the entire population as a sample (census). Data collection techniques were carried out by distributing questionnaires to 60 respondents and conducting unstructured interviews. This type of research is descriptive quantitative. The analysis technique used is multiple linear regression using SPSS version 29. The results of the analysis show that product quality partially has a positive effect on purchasing decisions (prob = 0.001 <0.05)., while price has no effect on purchasing decisions (0.080> 0.05). Product quality and price simultaneously have a positive effect on purchasing decisions (prob = 0.001 <0.05).